Visual Impairment, Eye Disease, and the 3-year Incidence of Depressive Symptoms: The Canadian Longitudinal Study on Aging. (2nd January 2021) - Grant, Alyssa; Aubin, Marie-Josée; Buhrmann, Ralf; Kergoat, Marie-Jeanne; Freeman, Ellen E.
ABSTRACT: Purpose: Our goal was to explore the longitudinal association between vision-related variables and incident depressive symptoms in a community-dwelling sample of older adults and to examine whether sex, education, or hearing loss act as effect modifiers. Methods: A 3-year prospective cohort study was performed using data from the Canadian Longitudinal Study on Aging consisting of 30, 097 individuals aged 45–85 years. Visual acuity was evaluated with habitual distance correction using an illuminated Early Treatment of Diabetic Retinopathy Study chart. Visual impairment was defined as binocular presenting visual acuity worse than 20/40. Incident depressive symptoms was defined using a cut-off score of 10 or greater on the Center for Epidemiologic Studies Depression scale. Participants were asked if they had ever had a physician diagnosis of age-related macular degeneration (AMD), glaucoma, or cataract. Multivariable Poisson regression was used. Results: Of 22, 558 participants without depressive symptoms at baseline, 7.7% developed depressive symptoms within 3 years. Cataract was associated with incident depressive symptoms (relative risk = 1.20, 95% confidence interval 1.05, 1.37) after adjusting for age, sex, income, education, partner status, smoking, level of comorbidity, hearing loss, and province. Visual impairment, AMD, and glaucoma were not associated with incident depressive symptoms. No effect modification was detected. Conclusions: Our longitudinal data confirm that the risk of depressive symptoms is higher in those who report ever having a cataract. Further research should confirm this and interventions should be considered.